Implementasi Kebijakan Pemerintah Dalam Manajemen Penanganan Sampah di Kota Ambon - Tuhumury, Sofpia; Laurens, Samson; Tuanaya, Wahab (LPPM Institut Pendidikan Nusantara Global, 2024)
This research was carried out in Ambon City at the Environment and Waste Service as well as several environmental and waste care communities/institutions in Ambon City. Primary data collection was carried out through interviews with a number of informants who were considered to be directly involved in the process of implementing government policies in waste management in Ambon City. The results of this research describe that the government's role in handling waste has not been effective, this is due to the lack of infrastructure which is inadequate to handle the increasing volume of waste in Ambon City and the lack of public awareness about the importance of good waste handling so that it is free from negative environmental impacts and this which is one of the inhibiting factors in the process of implementing government policies.